Smart Campus Development: Trends in Building a Digital-Based Academic Culture in Cyber Learning Environments - Fitri, Agus; Hasanah, Uswatun (Publisher Cv. Inara, 2024)
This research aims to formulate the design, roadmap, implementation and impact of smart campus development in higher education in building a digital-based academic culture. This research uses qualitative field research methods with a multi-site study design and flow analysis techniques. The findings of this research show that the smart campus development strategy has a special character in higher education. Smart campus development system design requires data center infrastructure, internet, and building management through Enterprise Architecture (EA) Analysis, Jason with Token (JWT), LemonLDA, and according to user interplace and user experience needs. The smart campus road map was built in a long-term plan towards smart people by relying on sustainable leadership through leadership policies. Smart campus implementation includes smart boards, multi-device gadgets, and campus domain e-mail ownership. The output of smart campus development has an impact on changing mindsets towards smart thinking and ease of serving the academic needs of both national and international students; accountability, transparency, certainty of academic processes and promotions; and compliance with the system.